Estudo teórico de nanofitas de grafeno dopadas com Ni e Mn - Rigo, Vagner Alexandre (2010)
In this work we present the results of a systematic study of the stability, and the electronic, stuctural and magnetic properties of graphene nanoribbons doped with Ni (Ni/GNR) and Mn (Mn/GNR), through ab initio density functional theory (DFT) calculations. Further, we analyse the electronic transport properties through the non-equilibrium Greens functions formalism (NEGF) coupled with DFT. The electronics and energetics of Si graphene-like monolayers and nanoribbons have also been studied. We determined the possible configurations of a Ni atom both adsorbed and substitutional in GNRs with zigzag edges. We show that the Ni atoms adsorb on the edges of the GNRs. This configuration is seen to be 0.3 eV lower in energy that the adsorption at the midlle of the GNR. The magnetic moments at the carbon atoms change due to the presence of the Ni, decreasing rapidly as the distance of the Ni atom decrease, recovering the value of the ideal GNR at 9 °A from the Ni atom. We obtained Ni d-levels inside a 1.0 eV energy window around the Fermi energy, leading to spin-dependent charge transport in the Ni/GNR. For the case of two Ni atoms adsorbed at the different edges of the GNR s, the antiferromagnetic coupling between both Ni atoms is energetically favored. For the case of the substitucional Ni atom, the edge position is also the energeticaly favored. It gives place to a spin-dependent charge transport, and suggest the use of these materials for spintronic devices. For the Mn doping in zigzag and armchair nanoribbons, it is shown that the edge site are the energetically favorable for adsorbed and substitucional Mn atoms. For the adsorbed Mn dimers, our calculations show that the sites along the border of the GNRs are the most stables ones. The distance between two Mn atoms of the adsorbed Mn2 is shorter than that for the isolated Mn2 molecule. For the zigzag nanoribbons, the magnetic moment of the Mn2 is not affected by magnetic state of the substrate, with the ground state being antiferromagnetic. The dimer/GNR configurations, Mn2/ferro A and Mn2/ferro F, show different elecrtonic properties. The Mn2/ferro A is seen to be semiconductor, while the Mn2/ferro F is semi-mettalic. These properties point to two interesting consequences: (i) the use of these systems as nanomemories, with the reading process made by measure of the electronic current through the nanoribbons and (ii) a spin-polarized current through the Mn2/GNR, with the control of the magnetization of the dimers. Finally, are show that H-passivate diamond-like Si monolayer and nanoribbons are semiconducting with low formation energies. Similarly to graphene, the non-H passivated Si monolayers, both planar and buckled, present linear dispersion of the ¼/¼¤ levels that cross at the Fermi energy.